Does the Implementation of Regulation Affect COVID-19 Transmissibility and Mortality? Lessons Learned from Nganjuk Regency - Danik Iga Prasiska; Sangchul Yoon (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2021)
Background: Coronavirus disease 2019 (COVID-19) as a global pandemic is ineluctable, transmission that originated from a foreign country became the local transmission in Indonesia. As several regional authorities implemented a large-scale social restriction policy to reduce the transmission of COVID-19, the Nganjuk Regency government chose to implement a different strategy with the implementation of Regent Regulation number 28 of 2020 about novel practice in the COVID-19 pandemic situation. Objective: This study aimed to analyze the impact of the implementation of the regulation on COVID-19 transmissibility and mortality at the Nganjuk Regency. Methods: Data were collected from the daily confirmed cases and death of COVID-19 made accessible for the public by the Nganjuk Regency Task Force for COVID-19 and Nganjuk Regency Health Office starting from March 30th to September 20th. Interrupted time series analysis was performed to estimate the impact of the implementation of regent regulation on COVID-19 transmission and mortality parameters. Result: The trend of new confirmed cases and deaths of COVID-19 in the Nganjuk Regency continued to fluctuate before and even after the implementation of regent regulation. It was found that there were reductions in case of fatality rates by -0.002 ± 0.003 (ρ 0.002) on CFR and -0.008 ± 0.008 (ρ 0.007) on eCFR after the regent regulation was implemented but there was no significant reduction on COVID-19 transmissibility parameter. Conclusion: Implementation of regent regulation in Nganjuk Regency significantly affected the reduction of case fatality rate but failed to slow down the COVID-19 transmissibility. Intensive community engagement to comply with the health preventive measures should be considered as an effective preventive strategy to reduce the transmission of COVID-19.